2006
DOI: 10.1080/10586458.2006.10128953
|View full text |Cite
|
Sign up to set email alerts
|

Random Matrix Theory and the Fourier Coefficients of Half-Integral-Weight Forms

Abstract: Conjectured links between the distribution of values taken by the characteristic polynomials of random orthogonal matrices and that for certain families of L-functions at the centre of the critical strip are used to motivate a series of conjectures concerning the value-distribution of the Fourier coefficients of half-integral weight modular forms related to these L-functions. Our conjectures may be viewed as being analogous to the Sato-Tate conjecture for integral weight modular forms. Numerical evidence is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…The T 3/4 has been predicted previously by Sarnak using different arguments, but random matrix theory adds more detailed information in the form of the power on the logarithm. For numerical evidence supporting the conjecture, see [9] and [10].…”
Section: Conjecture 11 (Conrey Keating Rubinstein Snaith)mentioning
confidence: 99%
See 1 more Smart Citation
“…The T 3/4 has been predicted previously by Sarnak using different arguments, but random matrix theory adds more detailed information in the form of the power on the logarithm. For numerical evidence supporting the conjecture, see [9] and [10].…”
Section: Conjecture 11 (Conrey Keating Rubinstein Snaith)mentioning
confidence: 99%
“…(The conjecture was originally stated in [9] with c E > 0, but in fact numerics have revealed that the constant can be zero [10] for certain families. An explanation of such a case with c E = 0 was given by Delaunay [14].)…”
Section: Conjecture 11 (Conrey Keating Rubinstein Snaith)mentioning
confidence: 99%
“…The constant α E depends on c −1/2 and the real period of E, but also on some extra subtle arithmetic information that seems to be related to Delaunay's heuristics for TateShafarevich groups [De] and is not yet fully understood. Numerical evidence in favour of this conjecture is presented in [CKRS2]. One can skirt these delicate issues, the power on the logarithm and the constant α E , as follows.…”
Section: 43mentioning
confidence: 99%
“…We see the values fluctuating about zero, most of the time agreeing to within about two percent. The convergence in X is predicted from secondary terms to be logarithmically slow and one gets a better fit by including more terms [CKRS2]. …”
Section: 43mentioning
confidence: 99%
See 1 more Smart Citation